Cybersecurity in Digital Supply Chains: A Narrative Review of Threats and Strategic Frameworks for Sustainable Logistics - Faisal, Ahmad; Cupiadi, Hedi; Sopannadi (Yayasan Sinergi Kawula Muda, 2024)
As global supply chains increasingly digitize their operations, cybersecurity in logistics information systems has become a critical concern. This study aims to synthesize current knowledge on cybersecurity threats, technological advancements, and strategic responses within the logistics sector. A structured narrative review was conducted using IEEE Xplore, Scopus, and Web of Science to identify relevant literature published between 2013 and 2024. The search utilized targeted Boolean combinations incorporating technical and operational keywords to ensure a holistic review. The findings highlight the prevalence of cyber threats such as ransomware, phishing, and DDoS attacks, which significantly affect operational continuity and data integrity. In response, emerging technologies such as blockchain and artificial intelligence are increasingly adopted to enhance detection, transparency, and risk mitigation. Despite these advancements, systemic challenges persist, including the reliance on legacy systems, regulatory fragmentation, and insufficient coordination between public and private sectors. This review emphasizes the need for integrated cybersecurity frameworks that align technical solutions with strategic policy reforms. Effective implementation requires not only technological innovation but also cross-sectoral collaboration, updated regulatory structures, and workforce development. Future research should explore empirical effectiveness, especially in diverse regional contexts, and investigate intersections between cybersecurity, sustainability, and governance. These insights offer a pathway toward resilient and secure logistics systems in a digitalized global economy.